Factors Predicting Treatment Outcome of Neonatal Sepsis In Hawassa University Comprehensive Specialized Hospital, Southern Ethiopia: A Retrospective Cohort Study - Gudeta Kaweti; Abebe Tamirat; Tihun Feleke (Iranian Journal of Neonatology, 2024)
Background: Neonatal sepsis is a systemic infection that affects newborns within the first 28 days of life. It has a significant effect on newborn mortality Worldwide. It could be responsible for as much as one-third of all neonatal deaths globally each year. The associated factors as well as clinical outcomes of neonatal sepsis are not well quantified. The aim of this study was to assess the treatment outcome and associated factors of Neonatal Sepsis in Hawassa University Comprehensive Specialized Hospital.Methods: A retrospective Cohort study was conducted. All neonates admitted to neonatal intensive care unit from July 28, 2014 to July 28, 2019 were included. The source of data was registration book and patients’ card. After being double checked for accuracy, data was entered into EpiData 3.1 and analyzed using SPSS version 22.  Testing for statistical association between the variables was done using bivariate and multivariate logistic regressions Poor treatment outcome includes refuse to take the treatment, development of complications, being referred to other health facilities and neonatal death.Results: All charts met enrollment criteria. More than three forth of the infants who treated were improved or recovered. Among the study participants, More than half were male and about half of them were younger than 3 days on admission. Majority of the mothers were found in the age group of 18 to 25 years. The poor treatment outcome for neonatal sepsis was high (16%). The predictors for poor treatment outcome of neonatal sepsis were being referred from other health facility (AOR=0.29, 95% CI: 0.24-0.89) and longer duration of treatment (AOR=0.36, 95% CI: 0.14-0.90).Conclusion: The poor outcome of neonatal sepsis was a significant health problem in the study area. Strengthening referral system and focusing on quality of care will improve poor outcome of neonatal sepsis.